2018
DOI: 10.1002/cbic.201800192
|View full text |Cite
|
Sign up to set email alerts
|

Protein Regulation by Intrinsically Disordered Regions: A Role for Subdomains in the IDR of the HIV‐1 Rev Protein

Abstract: Intrinsically disordered regions (IDRs) in proteins are highly abundant, but they are still commonly viewed as long stretches of polar, solvent-accessible residues. Here we show that the disordered C-terminal domain (CTD) of HIV-1 Rev has two subregions that carry out two distinct complementary roles of regulating protein oligomerization and contributing to stability. We propose that this takes place through a delicate balance between charged and hydrophobic residues within the IDR. This means that mutations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Indeed, bioinformatics studies of eukaryotic IDRs have suggested that these highly solvent-accessible regions are subject to significantly higher post-translational modifications than ordered protein regions (Xie et al 2007;Tompa 2014;Faust et al 2018). Although IDRs are generally thought to function based on the precise balance of, but not particular sequence of, positive, negative, polar, and hydrophobic residues (Faust et al 2018), both Hsf1, the primary heat shock transcription factor in eukaryotes, and Pop2, the conserved exonuclease of the Ccr4-Not complex, were found to have phosphorylation events at specific serine residues within their respective IDRs that regulate their function (Guettouche et al 2005;Yamamoto et al 2008;Lien et al 2019). Experimentally, Sis1's G/F region, Ydj1's G/F region, and Apj1's QS region have already been found to completely lack phosphorylation and ubiquitination (Swaney et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, bioinformatics studies of eukaryotic IDRs have suggested that these highly solvent-accessible regions are subject to significantly higher post-translational modifications than ordered protein regions (Xie et al 2007;Tompa 2014;Faust et al 2018). Although IDRs are generally thought to function based on the precise balance of, but not particular sequence of, positive, negative, polar, and hydrophobic residues (Faust et al 2018), both Hsf1, the primary heat shock transcription factor in eukaryotes, and Pop2, the conserved exonuclease of the Ccr4-Not complex, were found to have phosphorylation events at specific serine residues within their respective IDRs that regulate their function (Guettouche et al 2005;Yamamoto et al 2008;Lien et al 2019). Experimentally, Sis1's G/F region, Ydj1's G/F region, and Apj1's QS region have already been found to completely lack phosphorylation and ubiquitination (Swaney et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…There are some cases where this issue gets especially important. For example, the stabilization induced by intrinsically disordered regions in the HIV-1 Rev protein has been reported [21]. In another example, stability changes have been described for nucleoplasmin depending on the length of the disordered tail in each subunit of the pentameric protein: a fifty-residue C-terminal deletion mutant showed lower thermal stability, whereas an eighty C-terminal deletion mutant showed higher thermal stability than the full-length protein [22].…”
Section: Discussionmentioning
confidence: 99%
“…Some consequences derived from the presence of IDRs and the direct connection between order/disorder and function in proteins are not fully understood yet. Disordered regions in particular contribute to protein stability and function, sometimes with a counterbalancing effect [19,20], and should be considered as functional regions and not just flexible stretches [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…However, the Rev CTD still remains mysterious due to its structural plasticity that forces researchers to either delete it or leave this region unresolved in order to obtain structural information [12]. Recent mutagenesis research suggests that the CTD may help stabilize Rev and prevent aggregation [173]. Conversely, an increase in HIV-1 fitness is observed when stop codons are included in the CTD, suggesting it may play an inhibitory role [174].…”
Section: The Rev C-terminal Domain Is Structurally Unresolvedmentioning
confidence: 99%